Mediastinal Synovial Sarcoma: A Case Report and Literature Review - Linda SL Cheng; Gary MK Tse; Wilson WL Li; TW Lee; Anthony PC Yim (Canadian Respiratory Journal)
Synovial sarcomas are uncommon soft tissue tumours. Immunohistochemistry and cytogenetic techniques are essential for proper diagnosis and differentiation from other spindle cell neoplasms. A case of mediastinal synovial sarcoma is described, of which the unusual location, diagnosis and treatment form the basis of this report.